E-PERPUS: Optimizing User Experience of Digital Library using Design Thinking Method - Jagad Budi Prasetyo; Irianto, Kurniawan D. (International Journal of Informatics and Computation, 2025)
The rapid growth of digital libraries in Indonesia highlights the need for applications that not only provide access to collections but also deliver an engaging and user-friendly experience. However, the E-Perpus application has received a relatively low user rating of 3.2/5 on the Play Store. This study addresses these challenges by applying the Design Thinking methodology to evaluate and improve the user experience of the application. The process involves five key stages: empathizing with users, defining core issues, generating ideas, developing prototypes, and conducting usability testing. In this study, we collected data through interviews, observations, and usability evaluation using the System Usability Scale (SUS). Twenty participants were involved in testing both the original and redesigned versions of the application. The redesigned prototype achieved an average SUS score of 81.875, categorized as “Excellent,” compared to baseline scores in prior studies (70.8, “Fair”). These results indicate significant improvements in navigation, interface clarity, and feature integration. Overall, this research demonstrates that the Design Thinking approach is effective in identifying user needs and providing practical solutions to enhance digital library user experiences.